2009
DOI: 10.1007/s11199-009-9712-7
|View full text |Cite
|
Sign up to set email alerts
|

The Joy of Sexism? A Multinational Investigation of Hostile and Benevolent Justifications for Gender Inequality and Their Relations to Subjective Well-Being

Abstract: Previous research on system justification theory suggests that beliefs that rationalize inequalities are related to subjective well-being. We examine how "complementary" (hostile and benevolent) justifications of gender inequality may serve a palliative function for both men and women. Using multilevel modeling and data from 32 countries (N's=362 to 5160), we find that relationships between hostile and benevolent justifications and life satisfaction are moderated by the degree of gender inequality at the natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
115
4
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 52 publications
14
115
4
10
Order By: Relevance
“…However, it may be very difficult to change these sexist beliefs, especially benevolent sexist attitudes, because benevolent sexism functions to prevent changes in sexism (Becker and Wright 2011 Swim et al 2005 [the USA]). People may prefer holding benevolently sexist attitudes because it may be associated with positive well-being of women and men (Naiper et al 2010 [the USA]). As earlier researchers have suggested, combating benevolent sexism may require some new strategies.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
“…However, it may be very difficult to change these sexist beliefs, especially benevolent sexist attitudes, because benevolent sexism functions to prevent changes in sexism (Becker and Wright 2011 Swim et al 2005 [the USA]). People may prefer holding benevolently sexist attitudes because it may be associated with positive well-being of women and men (Naiper et al 2010 [the USA]). As earlier researchers have suggested, combating benevolent sexism may require some new strategies.…”
Section: Discussion and Suggestions For Future Researchmentioning
confidence: 99%
“…Dobronamerni seksizem je za ženske torej napovednik zadovoljstva z življenjem prek mehanizmov upravičevanja sistema, pri moških pa predstavlja neposredni napovednik zadovoljstva. Sovražni seksizem se pozitivno povezuje z zadovoljstvom z življenjem žensk in moških le v tistih družbah, kjer je neenakost med spoloma največja (Hammond in Sibley, 2011;Napier, Thorisdottir in Jost, 2010). Čeprav je splošna raven enakosti med spoloma pozitivno povezana s psihološkim blagostanjem žensk in moških, pa ima objektivna neenakost negativen vpliv na subjektivno blagostanje le v primeru, če posamezniki ne prevrednotijo neenakosti kot pravične in zaželene (Napier idr., 2010).…”
Section: Družbene Posledice Ambivalentnega Seksizmaunclassified
“…Thus, it is not surprising that these women believe that sexism is no longer a problem (i.e., endorse modern sexism; Zucker & Bay-Cheng, 2010). Similarly, in that ambivalent sexism portrays gender roles as ''complementary but equal,'' it preserves the status quo by coloring it as fair (Napier, Thorisdottir, & Jost, 2010). As such, neoliberals may have ambivalent sexist beliefs and support a sexual double standard not because they believe that men and women are unequal and should be treated as such (as in the case of nonfeminists, who do not believe in equality between the sexes; Zucker, 2004), but because these attitudes reflect their system-justifying beliefs and reinforce their egalitarian worldview.…”
Section: Defining Nonlabelersmentioning
confidence: 99%
“…Perhaps this is why neoliberals in the present study reported the highest levels of benevolent sexism: because of their faith in the current system, benevolent sexism-which involves superficially positive attitudes toward women that reinforce traditional gender role conformity (Glick & Fiske, 1996)-is less an issue of equality and instead, more reflective of their endorsement of the status quo. To neoliberals, benevolent sexism may not be perceived as bad since, by its very nature, this form of sexism serves a palliative, system-justifying purpose and reinforces their ''all is well'' perspective (Jost & Kay, 2005;Napier et al, 2010). Despite this optimistic worldview, research suggests that neoliberalism may nonetheless lead to negative consequences for minorities, both at the individual (e.g., Foster, Sloto, & Ruby, 2006;Major, Kaiser, O'Brien, & McCoy, 2007) and societal (Coburn, 2000;Foster et al, 2006;Nafstad, Blakar, Carlquist, Phelps, & Rand-Hendriksen, 2009) level.…”
Section: Implications For Women's Personal and Collective Well-beingmentioning
confidence: 99%